Probing conformational dynamics of an enzymatic active site by an in situ single fluorogenic probe under piconewton force manipulation - Pal, Nibedita (Proc Natl Acad Sci U S A, 2016)
Unraveling the conformational details of an enzyme during the essential steps of a catalytic reaction (i.e., enzyme–substrate interaction, enzyme–substrate active complex formation, nascent product formation, and product release) is challenging due to the transient nature of intermediate conformational states, conformational fluctuations, and the associated complex dynamics. Here we report our study on the conformational dynamics of horseradish peroxidase using single-molecule multiparameter photon time-stamping spectroscopy with mechanical force manipulation, a newly developed single-molecule fluorescence imaging magnetic tweezers nanoscopic approach. A nascent-formed fluorogenic product molecule serves as a probe, perfectly fitting in the enzymatic reaction active site for probing the enzymatic conformational dynamics. Interestingly, the product releasing dynamics shows the complex conformational behavior with multiple product releasing pathways. However, under magnetic force manipulation, the complex nature of the multiple product releasing pathways disappears and more simplistic conformations of the active site are populated.